Proceedings of the 28th International Conference on Computational Linguistics 2020
DOI: 10.18653/v1/2020.coling-main.540
|View full text |Cite
|
Sign up to set email alerts
|

Fact vs. Opinion: the Role of Argumentation Features in News Classification

Abstract: A 2018 study led by the Media Insight Project showed that most journalists think that a clear marking of what is news reporting and what is commentary or opinion (e.g., editorial, op-ed) is essential for gaining public trust. We present an approach to classify news articles into news stories (i.e., reporting of factual information) and opinion pieces using models that aim to supplement the article content representation with argumentation features. Our hypothesis is that the nature of argumentative discourse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This conceptualization enables us to add evidence estimating the audience's perception to the established newsroom-centered research. In addition, complementing the previous computational linguistic studies on news classification and formality detection (Alhindi, Muresan, and Preot ¸iuc-Pietro 2020;Pavlick and Tetreault 2016), this study sheds light on the "demand-side" with rather subjective annotations provided by actual news consumers (Costera Meijer 2020).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This conceptualization enables us to add evidence estimating the audience's perception to the established newsroom-centered research. In addition, complementing the previous computational linguistic studies on news classification and formality detection (Alhindi, Muresan, and Preot ¸iuc-Pietro 2020;Pavlick and Tetreault 2016), this study sheds light on the "demand-side" with rather subjective annotations provided by actual news consumers (Costera Meijer 2020).…”
Section: Discussionmentioning
confidence: 70%
“…Following Alhindi, Muresan, and Preot ¸iuc-Pietro (2020), we chose the BERT model for sentence classification in both tasks (Devlin et al 2018). To be more context-specific, a monolingual Dutch model (i.e., BERTje) that based on a diverse dataset containing three news corpora was chosen over the original one that only based on Wikipedia text (De Vries et al 2019).…”
Section: Model Trainingmentioning
confidence: 99%
“…These earlier approaches rely on engineered lexical features which are not robust against changes in topics and not generalisable to unseen (during training) news publishers. Recently, Alhindi et al ( 2020 ) combine argumentation features and computational language models like BERT 6 (Devlin et al, 2019 ) to identify news vs. opinion. They show promising performance in comparison to previous approaches across datasets and publishers.…”
Section: Discussionmentioning
confidence: 99%
“…From an empirical perspective, a few studies have leveraged argumentative features with the overall goal of advancing fake news detection. Alhindi et al (2020) have shown that argumentative components constitute relevant features to build classifiers able to automatically distinguish opinion articles from news stories and, thus, help fact checkers distinguishing facts from opinions. Focusing on semantic content rather than genre, Kotonya and Toni (2019) have built a system for stance detection that aggregates multiple stance labels from different text sources upon a claim to predict its veracity, assuming that (dis)agreement expressed by sources with high credibility is tied to claim trustworthiness.…”
Section: Argumentation and Fake Newsmentioning
confidence: 99%